First report of foodborne botulism due to Clostridium botulinum type A(B) from vegetarian home-canned pate in Hanoi, Vietnam. (October 2022) - Hoang, Le Huy; Nga, Tang Thi; Tram, Nguyen Thuy; Trang, Le Thi; Ha, Hoang Thi Thu; Hoang, Tran Huy; Anh, Dang Duc; Yen, Pham Bao; Nguyen, Nguyen Trung; Morita, Masatomo; Kenri, Tsuyoshi; Senoh, Mitsutoshi
Abstract: Even one case of foodborne botulism constitutes a public health emergency. We report a series of cases with delayed treatment due to delayed diagnosis. Clostridium botulinum type A(B) was isolated from vegetarian home-canned pate, but not from stool samples. These are the first recorded cases of foodborne botulism in Hanoi. Highlights: This report describes the first recorded cases of foodborne botulism in Hanoi. Clostridium botulinum was isolated from a vegetarian, home-canned pate. The isolate was characterized biochemically and genetically. The isolate belongs to group I. It carries the complete bont/A gene and an incomplete bont/B gene.